2011
DOI: 10.4018/jea.2011070102
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Dimensional Factors Impacting on E-Government Adoption in Botswana, Mozambique and Malawi

Abstract: With widespread adoption of ICT usage in public service delivery platforms (e-Government) throughout the world, African countries have vowed not to be left behind in this marathon. Robust e-Government adoption depends on the strategy employed to implement it. This paper presents the different initiatives that have been employed to promote e-Government development and development in Botswana, Mozambique and Malawi thereby showing the impact of such initiatives on overall e-Government agenda. Using extensive doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The main support theories used in literatures: The most popular theories used in literatures are TRA (the Theory of Reasoned Action, TRA) (AlAwadhi and Morris, 2009;Bwalya et al, 2011), TPB (the Theory of Planned Behavior, TPB) (Shareef and Kumar, 2011;Ozkan and Kanat, 2011;AlAwadhi and Morris, 2009), TAM (the Technology Acceptance Model, TAM) (Lin et al, 2011;Zafiropoulos et al, 2012;Sang et al, 2009a;Shareef and Kumar, 2011;Ozkan and Kanat, 2011;Orgeron and Goodman, 2011;Bwalya, 2009), TAM2 or ETAM (Zafiropoulos et al, 2012;Ebrahim and Irani, 2005;Bwalya, 2009), UTAUT (the Unified Theory of Acceptance and Use of Technology, UTAUT) (Bwalya, 2009;AlAwadhi and Morris, 2009;Alomari et al, 2012), DOI (the Diffusion of Innovation, DOI) (Zafiropoulos et al, 2012;Bwalya, 2009;Shareef and Kumar, 2011;Alhussain and Drew, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The main support theories used in literatures: The most popular theories used in literatures are TRA (the Theory of Reasoned Action, TRA) (AlAwadhi and Morris, 2009;Bwalya et al, 2011), TPB (the Theory of Planned Behavior, TPB) (Shareef and Kumar, 2011;Ozkan and Kanat, 2011;AlAwadhi and Morris, 2009), TAM (the Technology Acceptance Model, TAM) (Lin et al, 2011;Zafiropoulos et al, 2012;Sang et al, 2009a;Shareef and Kumar, 2011;Ozkan and Kanat, 2011;Orgeron and Goodman, 2011;Bwalya, 2009), TAM2 or ETAM (Zafiropoulos et al, 2012;Ebrahim and Irani, 2005;Bwalya, 2009), UTAUT (the Unified Theory of Acceptance and Use of Technology, UTAUT) (Bwalya, 2009;AlAwadhi and Morris, 2009;Alomari et al, 2012), DOI (the Diffusion of Innovation, DOI) (Zafiropoulos et al, 2012;Bwalya, 2009;Shareef and Kumar, 2011;Alhussain and Drew, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schultz (2001) appeals that E-government should take a user service approach to realize the usability and notes that the government website presented to citizens should just like an array of service navigation, which users can easily manipulate. Internal navigation function can be strengthened by setting up website map and internal search engine, by which users can easily skip the information that is not what users are interested in and get what they wanted effortlessly (Bwalya et al, 2011). Auxiliary navigation tools such as menu, directory, control button, theme tree, view map are quite useful for the navigation of website (Zafiropoulos et al, 2012).…”
Section: Citizen Adoption: Government Adoption To Citizen Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-government initiatives may be introduced to support areas such as health, agriculture, education and local government (Mutula, 2002). However, a study on adoption of e-government indicated that Malawi was facing challenges in areas of ICT policies, trust in use of web-based applications, availability of ICT facilities and lack of ICT skills, all of which were inhibiting users from engaging in e-government (Bwalya, Du Plessis, & Rensleigh, 2011).…”
Section: Ict Diffusionmentioning
confidence: 99%
“…The adoption of e-governance seems to have improved throughout the years (Rohkan, 2011;Bwalya et al, 2011). Reasons for this improvement include an increase in the level of awareness of the government and the citizens, as well as consequent active and proactive steps by both parties to achieve success.…”
Section: Introductionmentioning
confidence: 99%